Lessons in Program Evaluation: The ACTV Batterer Program Study and Its Claims. (April 2019) - Gondolf, Edward W.; Bennett, Larry; Mankowski, Eric
The "Evaluation of the Acceptance and Commitment Therapy (ACT) curriculum for domestic violence offenders" illustrates the methodological issues associated with interpreting program evaluations and applying them to policy. Despite the "preliminary" evidence, the authors promote ACTV as more effective in terms of recidivism compared with DU/CBT (cognitive-behavioral therapy) programming. A more critical consideration of the research, however, exposes further limitations that counter the initial speculations and interpretations of the study outcome. Consequently, the effectiveness of ACTV over the DU/CBT option remains in question and raises the need for a broader discourse on program effectiveness.